Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/pbi.13190
|View full text |Cite
|
Sign up to set email alerts
|

GbCYP86A1‐1 from Gossypium barbadense positively regulates defence against Verticillium dahliae by cell wall modification and activation of immune pathways

Abstract: SummarySuberin acts as stress‐induced antipathogen barrier in the root cell wall. CYP86A1 encodes cytochrome P450 fatty acid ω‐hydroxylase, which has been reported to be a key enzyme for suberin biosynthesis; however, its role in resistance to fungi and the mechanisms related to immune responses remain unknown. Here, we identified a disease resistance‐related gene, GbCYP86A1‐1, from Gossypium barbadense cv. Hai7124. There were three homologs of GbCYP86A1 in cotton, which are specifically expressed in roots and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 79 publications
1
25
0
Order By: Relevance
“…In this study, the histochemical observations showed that O. taihangensis roots underwent strong suberin depositions in both endodermal and exodermal cell walls in response to drought stress (Fig. 2), which was also observed in grapevine, barley and Gossypium barbadense [64][65][66] . Correspondingly, genes encoding cytochrome P450 enzymes (CYP86A1), fatty acyl reductase (FAR4), and long-chain acyl-CoA synthetase (LACS1) involved in the suberin biosynthesis pathway were upregulated in the drought-stressed roots of O. taihangensis (Fig.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In this study, the histochemical observations showed that O. taihangensis roots underwent strong suberin depositions in both endodermal and exodermal cell walls in response to drought stress (Fig. 2), which was also observed in grapevine, barley and Gossypium barbadense [64][65][66] . Correspondingly, genes encoding cytochrome P450 enzymes (CYP86A1), fatty acyl reductase (FAR4), and long-chain acyl-CoA synthetase (LACS1) involved in the suberin biosynthesis pathway were upregulated in the drought-stressed roots of O. taihangensis (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…In Arabidopsis, CYP86A1 and FAR4, which are expressed in the roots, have been identified as key genes for root suberin biosynthesis 67,68 . For example, the overexpression of GbCYP86A1-1 in Arabidopsis enabled transgenic lines to accumulate more suberin in the roots than the control 66 . In addition, in the FAR4 loss-of-function mutants, individual chain lengths of primary alcohols of root suberin were significantly reduced 68 .…”
Section: Discussionmentioning
confidence: 99%
“…Plant defense responses to colonization by pathogenic fungi usually involve the induction of enzymes that can degrade the fungal cell wall, as well as pathogenesis-related (PR) proteins and proteins involved in plant cell wall modification [ 57 , 58 ]. Although two PR proteins were found by proteomics to be more expressed in mycorrhizal roots of O. maculata , transcriptomic data indicated that plant defense responses were lower in mycorrhizal roots than in non-mycorrhizal roots.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms in response to pathogen attack are divided into two groups, pre-existing and induced. The pre-existing mechanisms mainly involve physical and chemical barriers for protecting plants from pathogen infestation at the first line, including the plant cuticle, cell wall, and antimicrobial compounds (Pieterse et al, 2009;Wang et al, 2019). Salicylic acid (SA) crosstalking with auxin, ethylene, and jasmonates (JA) is crucial for the inducible response of plants to pathogens infection including systemic acquired resistance and induced systemic resistance (Pieterse et al, 1998;Lopez et al, 2008;Vlot et al, 2009).…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%